A high calorie diet induces type 2 diabetes in the desert sand rat (Psammomys obesus) - El Aoufi, S.; Gendre, P.; Sennoune, S.R.; Rigoard, P.; Maixent, J.M.; Griene, L. (Cellular and Molecular Biology, 2007)
Diabetes mellitus type 2 is a major factor for cardiovascular diseases. The toxic effects of chronic hyperglycemia involve many alterations in the vascular tissue, including atherosclerosis. The pathogenesis of atherosclerosis in the diabetic syndrome (DS-II) has not been fully elucidated. A better understanding of the progress of DS-II at the level of the aorta could help us to identify inhibitors of atherosclerosis. Studies have shown that obesity and high calorie diet (HCD) are associated with the development of DS-II, however the lack of naturally occurring experimental models of DS-II have impaired to directly address these issues. We hypothesize that a HCD induces DS-II. This study (15 months duration) is designed to determine if HCD induces DS-II in the desert sand rat (Psammomys obesus; P. obesus). We also evaluated the histopathology of the aorta in animals fed with a laboratory chow pellets ad libitum (hypercaloric) and in control (animals fed with the naturally occurring hypocaloric diet; halophile plants). The weight and blood chemistry (glucose, lipids, and insulin levels) were evaluated periodically (once per week), and the histology of the aortas of these animals were assessed every 3 months for up to 12 months, during the development of DS-II. This study demonstrates that 40% of the animals in HCD develop DS-II at 3 months. Histological characterization demonstrates the typical alterations observed in atherosclerosis, i.e., alteration of the elastic fibers of the media layer and enrichment in collagen and glucosaminoglycans. This study demonstrates that P. obesus is an excellent animal model to study the progression of DS-II and the development of atherosclerosis.